Implementasi Syariah dalam Sistem Ekonomi dan Keuangan - Maula, Faruq Habibil (Maliki Interdisciplinary Journal, 2025)
Islamic economics and finance have emerged as alternatives to the global economic system. This article examines the application of sharia principles in economic and financial sectors, focusing on key instruments such as Islamic banking, sukuk, and zakat. The study identifies challenges and opportunities in implementing this system, emphasizing the need for robust regulation and improved public literacy. Using a qualitative approach, this research aims to provide insights into how sharia principles can enhance financial inclusion and promote economic justice